ANALISIS SISTEM KERJA DAN PENGARUH NON INVASIVE BLOOD PRESSURE PADA PATIENT MONITOR - Ulina, Sri; Nazara, Defi Purnama (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2023)
Patient Monitor is a device that monitors physiological conditions in the form of NIBP (Non-Ivasive Blood Pressure) blood pressure, temperature, respiration, SPO2 and the shape of the heart pulse continuously. The purpose of this study was to find out how the system works and the use of Non Iinvasive Blood Pressure is good in order to get maximum results. This research is a descriptive and qualitative method, namely by analyzing the Work System and the Effect of Noun Invasive Blood Pressure measurement on the Patient Monitor. The results obtained are the NIBP working system on the patient monitor device consisting of power supply, motor, air valve, microprocessor, display. The blood pressure measurement system uses a cuff with air pressure generated by a motor. The conclusion of this study is that the NIBP works using a pneumatic system, namely using air pressure, where the cuff is inflated until the pressure reaches a maximum above systolic pressure, where the arteries are effectively blocked. Then the cuff pressure is reduced to a constant level, the pressure traducer provides an analog signal to the digital hardware during the process of obtaining the systolic, diastolic and mean pressures.